Qualitätsmanagement jenseits von Checklisten Wie Qualitätsmanagement in der Praxis wirklich Nutzen bringt - Bellabarba, Julia; Kuch, Christine (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2009)
Quality management is often equated with bureaucracy, control and standardization. But QM can do more. This practical and implementation-oriented book is aimed at all doctors, psychotherapists and managers in health organizations who want to improve the management of their organization and who know that the formal processing of checklists, sample documents and flowcharts alone will not help them. The authors are familiar with the subject through their own practice and through advising outpatient structures. They present the legal framework, fundamentals, tools and practical implementation strategies to everyone who wants to use quality management in a way that quality management does not produce a "documentation graveyard", but a lively, development-oriented practice organization. The practice book accompanies the reader from the legal guideline to a solution-oriented health organization and shows that quality management benefits the small practice as well as the large medical organization. The book offers: - Clarity about the formal legal requirements - Structured QM implementation strategies in different organizational forms - Application-oriented descriptions of QM tools and QM measures for practice - Explanations and examples for improving communication, trust and commitment in practice - Practical examples of complex QM projects in medical practices, medical networks and other outpatient organizations